2017
DOI: 10.3311/ppme.11382
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Aiding and Opposing Thermal Buoyancy on Downward Flow around a Confined Circular Cylinder

Abstract: In this paper, two-dimensional

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…In order to get accurate results of the interaction between flow and wall of cylinders, the mesh points have a concentration distribution close to cylinders. The methodology of getting mesh is the same used in our previous works (Laidoudi and Bouzit, 2017c).…”
Section: Numerical Methodologymentioning
confidence: 99%
“…In order to get accurate results of the interaction between flow and wall of cylinders, the mesh points have a concentration distribution close to cylinders. The methodology of getting mesh is the same used in our previous works (Laidoudi and Bouzit, 2017c).…”
Section: Numerical Methodologymentioning
confidence: 99%
“…Studies have shown that the heat transfer of fluids is related to a set of criteria mainly connected to the geometric shape of the system and the fluid quality (Maneengam et al 2022;Laidoudi and Bouzit 2018;Aliouane et al 2021;Selimefendigil 2019;Alsabery et al 2020;Gangawane et al 2018). Geometry has an effect on the fluid motion allowing for an effect on heat transfer (Laidoudi and Bouzit 2017;Herouz et al 2022;Anouar and Mokhefi 2022;Laidoudi, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, there have been a significant number of researches aimed at studying the heat transfer within thermal exchangers (Mokeddem et al 2019;Alam and Kim 2018;Shirvan et al 2016;Laidoudi and Bouzit 2017a;Nguyen and Ahn 2021). The papers can be classified into two main groups: the first group is concerned with studying the geometry of the heat exchanger (Zimparov 2001;Laidoudi and Bouzit 2018;Kukulka et al 2011;Fan et al 2009;He et al 2019), while the second aims to examine the effect of the fluid quality (Aliouane et al 2021;Aissa et al 2022a;Aissa et al 2022b;Laidoudi et al 2022;Laidoudi and Ameur 2022b). Previous work has been achieved either through real experimental (Peyghambarzadeh et al 2011;Liu et al 2006;Bouvier et al 2003) or through numerical simulations (Laidoudi 2020a;Herouz et al 2023;Mohammed et al 2011).…”
Section: Introductionmentioning
confidence: 99%